2017
DOI: 10.1016/j.neuint.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

From dysfunctional endoplasmic reticulum-mitochondria coupling to neurodegeneration

Abstract: Over the last years, contact sites between the endoplasmic reticulum (ER) and mitochondria have attracted great attention in the study of cell homeostasis and dysfunction, especially in the context of neurodegenerative disorders. This is largely due to the critical involvement of this subcellular compartment in a plethora of vital cellular functions: Ca 2+ homeostasis, mitochondrial dynamics, transport, bioenergetics and turnover, ER stress, apoptotic signaling and inflammation. An increasing number of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 145 publications
0
37
0
Order By: Relevance
“…Because Miro1 contains Ca 2+ ‐sensing EF hand domains, local Ca 2+ concentrations regulate mitochondrial motility. Mitochondria buffer Ca 2+ and exchange Ca 2+ content with the endoplasmic reticulum (ER) in regions known as mitochondrial‐associated ER membranes (MAM), which influences mitochondrial motility and downstream mechanisms such as synaptic transmission and mitophagy . Indeed, Gelmetti et al have recently demonstrated in human cell models that under mitophagic stimuli, PINK1 relocalize at MAM and may promote ER‐mitochondria tethering.…”
Section: Introductionmentioning
confidence: 99%
“…Because Miro1 contains Ca 2+ ‐sensing EF hand domains, local Ca 2+ concentrations regulate mitochondrial motility. Mitochondria buffer Ca 2+ and exchange Ca 2+ content with the endoplasmic reticulum (ER) in regions known as mitochondrial‐associated ER membranes (MAM), which influences mitochondrial motility and downstream mechanisms such as synaptic transmission and mitophagy . Indeed, Gelmetti et al have recently demonstrated in human cell models that under mitophagic stimuli, PINK1 relocalize at MAM and may promote ER‐mitochondria tethering.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria support diverse cellular functions such as the formation of reactive oxygen species, ATP generation and apoptosis. 40 Mitochondrial dysfunction is a common feature in neurodegenerative disease, including Alzheimer's and Parkinson's disease. [41][42][43] Therefore, the observed ultrastructural defects in the hippocampus may be related to the decits in learning and memory induced by 60 Co-g irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of proteostasis is accompanied by the formation of Lewy bodies, a hallmark of PD and other dementias. To date, familial PD has been associated with dysregulated activity at the ER–mitochondria interface . Further research is needed to decide the effects of different PD‐related mutations on ER–mitochondria communication and how these may contribute to neurodegeneration in PD …”
Section: Abnormal Er–mitochondrial Crosstalk In Neurological Disordersmentioning
confidence: 99%
“…In the 1950s, the physical interaction between the ER and mitochondria was first identified in rat tissues, and later in yeast; and recently this has been evaluated in plants . The interorganelle ER–mitochondria interactions are mediated by tethering proteins, and tethering plays an important role in multiple cellular pathways, highlighted by the fact that perturbations are associated with several diseases, including cancer, metabolic diseases, and neurological disorders …”
Section: Introductionmentioning
confidence: 99%